Training and education of young physicians and engineers in the field of endoscopy and laparoscopy-a review of Germany-wide joint cooperation and training possibilities - Wichmann, Dörte; Duckwort-Mothes, Benedikt; Hirt, Bernhard; Wilhelm, Dirk; Steger, Jana; Zweimüller, Martin; Küllmer, Armin; Raithel, Martin; Maiss, Jürgen; Pott, Peter; Wittenberg, Thomas (Current Directions in Biomedical Engineering, 2023)
Introduction: Application-related (hands-on) training and instruction is an essential component in the advanced education of physicians in residency. To teach and train required endoscopic examinations and interventions in a standardized manner, courses are offered by various societies. Within these courses the assistant endoscopists learn and train how to use the technical equipment and how to perform the examinations and related interventions. Similarly, for graduate biomedical engineering students with a job-or research-related interest in the field of endoand laparoscopy, an early involvement and practical introduction to the instrumentation and techniques-if possible already during their studies-can generate a fundamental understanding of the technical requirements as well needs of the physicians. Objective: As various such (hands-on) training-courses for flexible and rigid endoscopy specifically addressing young physicians, surgeons as well as engineers are offered by numerous institutes, this contribution tries do provide a structured overview on/over these possibilities. Material: Known cross-institutional courses in the field of endo-and laparoscopy currently offered in Germany in cooperation of physicians and engineers are listed and briefly described. Results: A total of n = 4 crossinstitutional courses for the introduction and training in flexible and rigid endoscopy have been identified. Discussion: The cross-institutional courses for physicians and technicians in the field of endo-and laparoscopy presented serve to provide a better understanding of the subject matter and the field of either discipline. Questions that arise in the field of endoscopy from physicians can be addressed at an early stage and, if necessary, worked on with little effort. Ideas for new instruments and even new interventions can arise and be pursued through an intensive exchange between technicians and physicians. Collaborations are established on a local basis which will foster national activities in this field and which allow to develop competencies relevant for the industrial sector of medical engineering.
CRIS-Team Scopus Importer:2023-10-20
Keywords: education; Endoscopy; hands-on training; interdisciplinary cooperation; laparoscopy